The Interrelationships among Transportation Services, Exports, Renewable Energy Consumption, Industrial Production, and Economic Growth: A Dynamic Panel Data Approach in BRICS Countries - Markhayeva, Bayanslu Akhilbekovna; Seitbekova, Saltanat Tursynovna; Mashirova, Tazhikul N.; Mergenbayeva, Aziza T.; Kydyrova, Zhamilya Sh.; Beisenova, Madina Unaibekovna; Taigashinova, Kusnikamal; Bolganbayev, Artur (International Journal of Energy Economics and Policy, 2026)
This study examines the relationships between transportation services, exports, renewable energy consumption, industrial production, and economic growth using data from BRICS countries (Brazil, Russia, India, China, and South Africa) for the period from 1994 to 2023. After assessing cross-sectional dependence and the stationarity of the data series, a dynamic panel data analysis was conducted. The results of the Hausman test confirmed the validity of the random effects model. The findings reveal that exports, industrial production, and renewable energy consumption have positive and statistically significant effects on economic growth. This indicates that enhancing production capacity and increasing the use of renewable energy contribute to long-term growth. Conversely, while the impact of transportation services on growth is positive, it was not statistically significant, suggesting that the effects of the transportation sector on economic growth are indirect and manifest over time. When analyzing country-fixed effects, it was found that economic growth is above the panel average for China and India, while it falls below the average for Brazil and Russia. In conclusion, the study suggests that a growth model focused on renewable energy, production, and exports is the most suitable approach for sustainable economic development in BRICS countries.